Some Questions About Labor Arbitration - Pierre R. Loiseaux (Washington University Law Quarterly, 1956)
One of the most important effects of the NLRA as amended by the LMRA is the growth of voluntary arbitration. Because the collective contract is governmentally imposed and because voluntary arbitration is a logical outgrowth of a continuing contractual relationship, unless there are available and feasible alternatives, the imposition of the collective contract has as a long term effect the development of labor arbitration to solve disputes otherwise unprovided for.
Keywords: Industrial arbitration